Dung or carrion? Sex and age determine resource attraction in dung beetles - Iannuzzi, Luciana; Maia, Artur Campos D.; González-Tokman, Daniel M.; Gomes, Andreza De Andrade Catunda; Cerqueira, Leonardo Vilas Bôas M.P.; Salomão, R. P. (Ecological Entomology, 2021)
1. Food choice may change depending on sex, age, and physiological condition due to nutritional requirements or because of mechanisms that promote food recognition. Among dung beetles, some species are attracted to both carrion and dung, but why males and females are more attracted to either resource remains unclear. This study aimed to investigate whether body size, physiological condition (body dry mass, lipid mass, muscle mass) and age (young, mature, old) affect resource attraction in males and females of two species of dung beetles, Dichotomius iannuzziae and D. gilletti. 2. This study was carried out in remnants of Atlantic Forest in Brazil. To evaluate resource attraction, pitfall traps baited with feces or carrion were installed in the remnants, and the beetles were categorized according to sex and age. Furthermore, beetles' physiological condition and body size were measured. 3. Population structure of D. iannuzziae differed according to bait type. Males of D. iannuzziae were more attracted to feces than carrion across all age classes. The same occurred among conspecific mature females, suggesting a sex-specific reproductive preference for feces. Contrastingly, D. gilletti resource attraction did not vary with sex or age. For both species, neither body size nor physiological condition defined resource attraction, indicating that compensatory feeding due to nutrient requirements is unlikely. 4. Due to the changes in food quality and quantity as a consequence of forest loss, mammal extinction and landscape transformation, it is critical to understand how wild species respond to different scenarios of food availability. © 2021 The Royal Entomological Society.
Keywords: Intraspecific competition; Scarabaeinae